The ChoicePoint Dilemma How Data Brokers Should Handle the Privacy of Personal Information. - Otto, P.N.
Before 2005, data broker ChoicePoint suffered fraudulent access to its databases that exposed thousands of customers' personal information. We examine Choice-Point's data breach, explore what went wrong from the perspective of consumers, executives, policy, and IT systems, and offer recommendations for the future.
Keywords: Choice-Point data breach; ChoicePoint data broker; IT system; Customer personal information privacy; Database fraudulent access